Proactive behaviors and managers' career success in Malaysian public sector organizations - Mohd Rasdi, Roziah; Ismail, Maimunah; Uli, Jegak; Garavan, Thomas N.; Mohd Noah, Sidek (2010)
Changes in the job market and individual occupational careers require managers to be more proactive than before if they want to succeed. The present research was conducted to examine the effect of proactive behaviors (i.e., individual career management, networking behavior and proficiency in computer skills) on objective and subjective career success. Using 288 samples of public sector managers, we found that individual career management was positively correlated to subjective career success alone, and computer skills was significantly but negatively related to objective career success only. In support of our hypothesis, we found that some of the networking variables have significantly explained both objective and subjective career success, whereas engaging in professional activities has contributed significantly to both measures of career success. Implications for research and human resource development are discussed.